110 minima timings of eclipsing binaries - Petropoulou, M.; Gazeas, K.; Tzouganatos, L.; Karampotsiou, E. (Information Bulletin on Variable Stars, 2015)
We present 110 times of minima of 23 eclipsing binaries.
Keywords: CCD photometry